Empowering Minds: Elevating Reading Comprehension in Tenth Grade Students with Direct Method - Huda, Khoirul; Misa, Mikhael (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2024)
Reading comprehension is a critical skill for academic success and lifelong learning. Direct instruction methods have gained attention for their effectiveness in improving reading comprehension outcomes among high school students. This study explores the significance of elevating reading comprehension in tenth grade through direct methods. The research design employed was collaborative Classroom Action Research (CAR), with the researcher serving as the observer while the classroom English teacher conducted the teaching and learning activities. The subjects of this research were tenth grade students of SMAN 3 Kefamenanu in the 2023/2024 academic year, consisting of 25 students: 9 males and 16 females. Data analysis involved both qualitative and quantitative techniques. Thematic analysis was used to evaluate the instructional strategies and their efficacy in enhancing reading comprehension. The results showed that all 25 students (100%) scored higher than the minimal passing grade of 76. Teaching students to employ these strategies consistently can significantly improve their reading comprehension skills, leading to better academic performance and a greater ability to engage with complex texts throughout their lives.